1973
DOI: 10.1104/pp.52.6.660
|View full text |Cite
|
Sign up to set email alerts
|

T-2 Toxin Decreases Logarithmic Growth Rates of Tobacco Callus Tissues

Abstract: T-2 toxin, a mycotoxin produced by Fusarium tricinctum, decreases logarithmic growth rates of tobacco (Nicotiana tabacum L.) pith callus tissues. Toxin concentrations as low as 0.003 ,uM will decrease growth rates; a concentration of 0.081 aM will halt growth completely. Additional exogenous cytokinin will reduce the inhibition by toxin only when the initial cytokinin and toxin concentrations are quite low (about 0.01 jaM). When inhibited tissues are transferred to media lacking toxin, they assume the faster, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This apparent reversal of inhibition would indicate that normal metabolic events could proceed, once Downloaded by [JAMES COOK UNIVERSITY] at 02:08 17 March 2015 (Helgeson et al 1973). Such an observation substantiates the probability of a direct toxic effect on AFBi exposure.…”
Section: Discussionsupporting
confidence: 51%
“…This apparent reversal of inhibition would indicate that normal metabolic events could proceed, once Downloaded by [JAMES COOK UNIVERSITY] at 02:08 17 March 2015 (Helgeson et al 1973). Such an observation substantiates the probability of a direct toxic effect on AFBi exposure.…”
Section: Discussionsupporting
confidence: 51%
“…In spite of the widespread natural occurrence of cytokinins and the diverse metabolic effects which they are now known to promote in both plants and animals (1-13), relatively little has been learned about their mechanism of action at the molecular level. This prompted the design and synthesis of a class of potent anticytokinins, structurally related to the cytokinins, in the hope that the antimetabolites might extend the study of cytokinins to new biological systems and provide useful information pertinent to the mechanism of cytokinin action (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the widespread natural occurrence of cytokinins and the diverse metabolic effects which they are now known to promote in both plants and animals (1-13), relatively little has been learned about their mechanism of action at the molecular level. This prompted the design and synthesis of a class of potent anticytokinins, structurally related to the cytokinins, in the hope that the antimetabolites might extend the study of cytokinins to new biological systems and provide useful information pertinent to the mechanism of cytokinin action (14)(15)(16)(17).On the basis of the similar effects obtained with N6-(A2-isopentenyl)adenosine and dibutyryl cyclic AMP, the cytokinins have been postulated to mediate their effects in phytohemagglutinin-treated human lymphocytes by involvement in cyclic AMP metabolism (13). This postulate was consistent with the finding that the cytokinin trans-zeatin ribonucleoside was inhibitory to the cyclic AMP phosphodiesterases from beef brain and crown-gall tumor cells, the latter of which was Abbreviations: Dibutyryl cyclic AM1P, N6,02'-(dibutyryl)adenosine cyclic 3': 5'-monophosphate; cyclic AMP, adenosine cyclic 3': 5'-monophosphate; trans-zeatin ribonucleoside, N6-(4-hydroxy-3-methyl-trans-2-butenyl)adenosine; 8-bromo …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vanderhoef and Key (16) and Vanderhoef et al (17) showed that cytokinin inhibited auxin-promoted elongation more severely than control elongation. On the other hand, Helgeson et al (6) have shown that T-2 toxin can decrease cytokinin-controlled growth rates in the tobacco callus After a 1-hr preincubation of 1-cm hypocotyl sections in toxin, tissue was transferred to the growth chamber. After 15 min auxin was added.…”
Section: Resultsmentioning
confidence: 99%